Introduction to social justice. (New York 3G E-LEARNING, 2019)
Social justice assigns rights and duties in the institutions of society, which enables people to receive the basic benefits and burdens of cooperation. This book takes a new approach to teaching students to think and learn about issues of race and diversity.
An introduction to social justice. -- The role of language in social justice. -- Organizational theory: challenges and opportunities. -- Social justice in major world religions. -- Social justice and leadership. -- Community-building: personal and community empowerment. -- Social justice and technology -- Index.
Includes bibliographical references and index
Keywords: Social justice; Social rights; Gender mainstreaming; Environmental justice; Justice -- History